Prolonging Disaster (Un)recovery: "Culturally‐Irrelevant" Fish Consumption Advisories in the Keweenaw Bay Indian Community. Issue 2 (1st December 2020) - Gagnon, Valoree S.
Abstract: The United States responded to the 1971 international mercury crisis by establishing fish consumption advisories, which were intended to warn the American public of temporary mercury contamination in fish. However, advisories remain implemented as public health protection measures in all fifty states. This perpetual reliance on advisories is prolonging disaster recovery, or more precisely, ensuring a continuous state of what I term "disaster (un)recovery." Modified approaches create "eat safe fish" guidance for fishers, producing "culturally‐relevant" recommendations. This means advisories offer a number of "healthy" choices that correspond to specific bodies of water and fish species favored by varying target populations. This article explores fish advisory policy in the Keweenaw Bay Indian Community (KBIC), a federally‐recognized Indian tribe that retains treaty‐established homelands and harvesting rights in the Lake Superior region. By using ethnographic and oral history methods, I examined fish harvest practices in an effort to create culturally‐relevant fish advisory recommendations for the community. However, my analysis reveals the cultural irrelevance of advisories as health protection measures for the KBIC. Examining cultural considerations within KBIC harvesting and in the development of fish advisories illustrates how the notion of "culture" actually leads to increased toxic exposure. The KBIC rely on fish for social and spiritual wellbeing, which simultaneously places their physical health at great risk. I argue that advisory policy as public health protection is primarily a social justice issue, and conclude by identifying pathways for culturally‐specific recovery.